The Private Rented Sectors in the North and South of Ireland: A Case Study in Convergence Analysis - Hayden, Aideen; Gray, Paddy; McAnulty, Ursula; Jordan, Bob (Journal of Economic Development, Environment and People, 2015)
The theme of this paper centres on the convergence and divergence of housing policy between two regimes inhabiting the same geographical space on the island of Ireland, as reflected in the development of the private rented sector (PRS) in both jurisdictions. Using a historical comparative analysis of key indicators, this paper aims not just to present an accurate picture of the state of policy towards the sector in both jurisdictions today, but to place this analysis within a framework which looks at the backdrop of overall housing systems. The paper postulates that while Northern Ireland and the South of Ireland are reflective of the Anglo Saxon tradition in housing, major historical differences in their pathways have brought clearly identifiable policy outcomes indicative of their differing status in comparative welfare analysis. While both jurisdictions have diverged significantly during the course of the twentieth century in the profile of policy and housing tenure mix, showing examples of path dependency at work, there is clear evidence of more recent convergence. More recent changes in housing policy in both jurisdictions away from direct social housing provision and the changing role of the private rented sector are also examined and a convergence theory is proposed.